Pharmacogenomics: Prescribing based on genetic variation. Issue 2 (February 2021) - Rafi, Imran; Hayward, Judith; Dawes, Martin
Clinical decision support systems relating to prescribing are available on general practice information technology systems, with warnings relating to drug–drug interactions and allergies. These tools can help us anticipate and avoid known side effects of drugs, but only after we have selected the drug. Combining these with renal function, liver function, other biophysical markers and pharmacogenomics information, can improve medicines optimisation and reduce adverse effects. Managing all these variables at the same time as conforming to disease guidelines is a challenge. The challenge is even greater when managing multi-morbidity and the associated polypharmacy.